2016
DOI: 10.1186/s13071-016-1408-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with tick bites and pathogen prevalence in ticks parasitizing humans in Georgia, USA

Abstract: BackgroundThe incidence and emergence of tick-borne diseases has increased dramatically in the United States during the past 30 years, yet few large-scale epidemiological studies have been performed on individuals bitten by ticks. Epidemiological information, including disease development, may provide valuable information regarding effectiveness of tick bite prevention education, pathogen transmission, human-disease dynamics, and potential implications for under reporting of tick-borne diseases.MethodsTicks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 41 publications
(30 reference statements)
1
21
0
Order By: Relevance
“…In field-collected A. maculatum, R. parkeri infection rates range from 5 to 52% (Hooker et al, 1912; Edwards et al, 2011; Varela-Stokes et al, 2011; Nadolny et al, 2014; Paddock and Goddard, 2015; Gleim et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In field-collected A. maculatum, R. parkeri infection rates range from 5 to 52% (Hooker et al, 1912; Edwards et al, 2011; Varela-Stokes et al, 2011; Nadolny et al, 2014; Paddock and Goddard, 2015; Gleim et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Contemporary field studies frequently detect alternative rickettsial species in A. maculatum , including Rickettsia amblyommatis , identified in 5% of ticks, and R. montanensis , a non-pathogenic endosymbiont RickettsiaRickettsia , detected in 14% of ticks (Lee et al, 2014; Gleim et al, 2016). However, whether A. maculatum is a competent host for these additional Rickettsia species remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A recent CDC survey found 25.4% of South Atlantic residents reported tick exposure in their household in the past year; 11.7% sought medical care [11]. A Georgia study examining 597 ticks submitted by 444 participants found 12 individuals fit requirements for possible tick-borne illnesses [12]. We could not find any retrospective reviews of tick bites and illness experience among lay individuals over time anywhere in the United States.…”
mentioning
confidence: 74%
“…Thus, 1.7% of the attached ticks were associated with presumed tick-related illness. Interestingly, the Georgia study with 597 ticks from 444 people found 2.7% developed a possible tick-borne illness [12]. The risk of presumed STARI varied considerably between the subjects even though each experienced a similar number of lone star tick bites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation